Pelaksanaan Hak Narapidana Wanita Berdasarkan Peraturan Pemerintah Republik Indonesia Nomor 32 Tahun 1999 tentang Syarat dan Tata Cara Pelaksanaan Hak Warga Binaan Pemasyarakatan di Lembaga Pemasyarakatan Perempuan Kelas IIB Padang - Sherly Alpines; Yulia Nizwana; Eri Arianto (AHKAM, 2026)
The fulfillment of the rights of female prisoners is an important issue in the correctional system because women have specific needs related to reproductive health, psychological conditions, social relations, pregnancy, breastfeeding, and social reintegration. This study aims to analyze the implementation of the rights of female prisoners based on Government Regulation Number 32 of 1999 at the Class IIB Padang Women’s Correctional Institution and to identify the obstacles and efforts to resolve them. This study used a sociological juridical method with a qualitative descriptive approach. The research informants included the Head of the Correctional Institution, officials responsible for guidance and registration, clinic nurses, work activity staff, and 50 female prisoners selected purposively. Data were collected through interviews, observation, and document study, and were then analyzed qualitatively through the stages of editing, coding, data presentation, and conclusion drawing. The results show that the fulfillment of the basic rights of female prisoners, such as the right to worship, receive proper food, obtain health services, participate in self-reliance training, receive remission, and undergo assimilation, has been implemented fairly well. However, its implementation still faces obstacles in the form of limited specific regulations, overcapacity, health facilities, budgets, the number of officers, and industrial partners. The conclusion of this study emphasizes that fulfilling the rights of female prisoners requires strengthening regulations, improving facilities, and expanding cross-sectoral cooperation. These findings contribute to the development of the concept of gender-based corrections and provide practical implications for improving the governance of correctional services that are more responsive to the specific needs of female prisoners.